2017
DOI: 10.1016/j.neuropharm.2017.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase 3 beta alters anxiety-, depression-, and addiction-related behaviors and neuronal activity in the nucleus accumbens shell

Abstract: Psychiatric disorders such as anxiety, depression and addiction are often comorbid brain pathologies thought to share common mechanistic biology. As part of the cortico-limbic circuit, the nucleus accumbens shell (NAcSh) plays a fundamental role in integrating information in the circuit, such that modulation of NAcSh circuitry alters anxiety, depression, and addiction-related behaviors. Intracellular kinase cascades in the NAcSh have proven important mediators of behavior. To investigate glycogen-synthase kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 78 publications
5
51
0
Order By: Relevance
“…Additionally, a similar pro-depression-like effect can be induced by GSK3β overexpression in the nucleus accumbens, while the expression of inactive GSK3β mutant promotes resilience to social defeat stress [46]. On the other hand, Crofton et al, found that the knockdown of GSK3β in the nucleus accumbens shell increases cocaine self-administration and depression-like behavior in social contact tests in rats [47,48]. This discrepancy between stressor type and its effect within the same structure is also reflected in the activity of the ventral tegmental area, a midbrain structure that delivers input to nucleus accumbens.…”
Section: Gsk3β Expression Profile and Activity In Depressionmentioning
confidence: 99%
“…Additionally, a similar pro-depression-like effect can be induced by GSK3β overexpression in the nucleus accumbens, while the expression of inactive GSK3β mutant promotes resilience to social defeat stress [46]. On the other hand, Crofton et al, found that the knockdown of GSK3β in the nucleus accumbens shell increases cocaine self-administration and depression-like behavior in social contact tests in rats [47,48]. This discrepancy between stressor type and its effect within the same structure is also reflected in the activity of the ventral tegmental area, a midbrain structure that delivers input to nucleus accumbens.…”
Section: Gsk3β Expression Profile and Activity In Depressionmentioning
confidence: 99%
“…Recently, a role for the nucleus accumbens (NAc), the main anatomical constituent of the ventral striatum (VS), is emerging in the context of anxiety (Gunaydin and Kreitzer, 2016;Levita et al, 2012) interconnected with the NAc function in behavioral adaptation (Haber and Behrens, 2014). In rodents, anxiety-like behaviors can be regulated by pharmacological (Heshmati et al, 2016;Lopes et al, 2012) or genetic (Crofton et al, 2017;Feng et al, 2017;Shen et al, 2016;Zhao and Gammie, 2018) manipulation of NAc neurochemistry. Importantly, anxiety-like behaviors have also been related to variations in NAc mitochondrial function Van Der Kooij et al, 2018) and brain energy metabolism (Larrieu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the swim trajectories revealed significant Drug × Trial Day interactions when Center Time [ F (6,60) = 2.3, p = 0.038] and Center Distance [ F (6,60) = 2.2, p = 0.04] were analyzed. By Trial Day 4, SB 216763 treatment resulted in the rats spending significantly more time in the center of the pool (SB vs. Veh, p = 0.023, Bonferroni post hoc , Figures 1D,E ) which may reflect an anxiolytic effect of the drug ( Crofton et al, 2017 ).…”
Section: Resultsmentioning
confidence: 98%